2016
DOI: 10.18632/oncotarget.10452
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA polymerase I transcription initiation by CX-5461 activates non-canonical ATM/ATR signaling

Abstract: RNA polymerase I (Pol I)-mediated transcription of the ribosomal RNA genes (rDNA) is confined to the nucleolus and is a rate-limiting step for cell growth and proliferation. Inhibition of Pol I by CX-5461 can selectively induce p53-mediated apoptosis of tumour cells in vivo. Currently, CX-5461 is in clinical trial for patients with advanced haematological malignancies (Peter Mac, Melbourne).Here we demonstrate that CX-5461 also induces p53-independent cell cycle checkpoints mediated by ATM/ATR signaling in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 84 publications
18
127
2
Order By: Relevance
“…THP-1 (p53null), SHI-1 (p53WT), and KG-1 (p53null) exhibited aberrant cell-cycle progression in response to CX-5461 with cells accumulating in late S and G2/M phase ( Figure 5A). In line with our recent study demonstrating CX-5461-mediated activation of ataxia telangiectasiamutated and Rad31-related kinase (ATM/ATR) signaling in the absence of global DNA damage in fibroblasts, 17 and consistent with aberrant G2/M transition, Pol I inhibition induced phosphorylation of the CHK1 on S345 and CHK2 threonine 68, which are ATM-/ATRdependent sites, respectively ( Figure 5B). Moreover, pharmacologic inhibition of ATM/ATR signaling partially rescued the delay in late S and the G2/M phase arrest in THP-1, SHI-1, and KG-1 cell lines ( Figure 5C-D).…”
Section: Cx-5461 Activates P53-independent Cell-cycle Checkpoint Signsupporting
confidence: 91%
See 1 more Smart Citation
“…THP-1 (p53null), SHI-1 (p53WT), and KG-1 (p53null) exhibited aberrant cell-cycle progression in response to CX-5461 with cells accumulating in late S and G2/M phase ( Figure 5A). In line with our recent study demonstrating CX-5461-mediated activation of ataxia telangiectasiamutated and Rad31-related kinase (ATM/ATR) signaling in the absence of global DNA damage in fibroblasts, 17 and consistent with aberrant G2/M transition, Pol I inhibition induced phosphorylation of the CHK1 on S345 and CHK2 threonine 68, which are ATM-/ATRdependent sites, respectively ( Figure 5B). Moreover, pharmacologic inhibition of ATM/ATR signaling partially rescued the delay in late S and the G2/M phase arrest in THP-1, SHI-1, and KG-1 cell lines ( Figure 5C-D).…”
Section: Cx-5461 Activates P53-independent Cell-cycle Checkpoint Signsupporting
confidence: 91%
“…These data, together with our previous studies, 8 demonstrate that acute inhibition of Pol I transcription leads to activation of multiple cell-cycle checkpoints 17 ; and specifically, a G1 checkpoint characterized by activation of p53 and a G2/M checkpoint associated with CHK1/ CHK2 signaling, downstream of ATM/ATR activation. Thus, mammalian cells appear to have evolved a number of mechanisms to monitor rRNA synthesis and inactivate cell-cycle progression if rRNA output does not match cellular demand.…”
Section: Discussionsupporting
confidence: 77%
“…While CX-5461 inhibits SL-1 interaction with Pol I and prevents Pol I recruitment to the rDNA promoter [56,57], it is also possible to inhibit Pol I transcription initiation…”
Section: Accepted Manuscript 20mentioning
confidence: 99%
“…Furthermore, we have recently demonstrated that acute treatment with CX-5461 (1 hour) induces chromatin defects at the rDNA associated with depletion of Pol I binding across the transcribed region, leading to activation of DNA damage signalling in the absence of global DNA damage [57]. Importantly, we reported improved therapeutic efficacy against lymphoma in vivo by combining CX-5461 with inhibitors of DNA damage signalling [57]. It is therefore likely that targeting Pol I transcription at multiple levels simultaneously (e.g., initiation / elongation and or rRNA processing) may further improve the efficacy of therapies targeting rDNA transcription.…”
Section: Accepted Manuscript 20mentioning
confidence: 99%
“…While p53 dependent nucleolar stress is well understood, more recent research by Quin et al[73] has identified p53 independent mechanisms involving activation of ATM/ATR signalling which occurs without the induction of global DNA damage[73]. Evidently, ribosome biogenesis is a highly complex and finely balanced process involving multiple key effectors.…”
Section: Ribosome Biogenesismentioning
confidence: 99%